2003
DOI: 10.1152/ajpheart.00610.2002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced baroreflex sensitivity in free-moving calponin knockout mice

Abstract: Masuki, Shizue, Michiko Takeoka, Shun'ichiro Taniguchi, and Hiroshi Nose. Enhanced baroreflex sensitivity in free-moving calponin knockout mice. Am J Physiol Heart Circ Physiol 284: H939-H946, 2003. First published November 14, 2002 10.1152/ajpheart.00610.2002Calponin is an actin binding protein in vascular smooth muscle that modifies contractile responses. However, its role in mean arterial pressure (MAP) regulation has not been clarified. To assess this, MAP and heart rate (HR) were measured in calponin knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
36
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 27 publications
7
36
0
Order By: Relevance
“…Besides the experimental considerations, it has to be pointed out that the estimates of BRS presently obtained using the recent methods were close to the maximal gain derived from the full baroreflex curves (roughly between 2 and 5 ms/mmHg) (22)(23)(24)29). The sequence technique (2,7,10,21,34) or the spectral method (gain of the transfer function or alpha coefficient) (2, 7, 9 -12, 16, 18, 32) also indicated values of BRS in the same order of magnitude as the present values, between 1 and 4 ms/mmHg.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Besides the experimental considerations, it has to be pointed out that the estimates of BRS presently obtained using the recent methods were close to the maximal gain derived from the full baroreflex curves (roughly between 2 and 5 ms/mmHg) (22)(23)(24)29). The sequence technique (2,7,10,21,34) or the spectral method (gain of the transfer function or alpha coefficient) (2, 7, 9 -12, 16, 18, 32) also indicated values of BRS in the same order of magnitude as the present values, between 1 and 4 ms/mmHg.…”
Section: Discussionsupporting
confidence: 56%
“…Masuki et al (22) and Martinka et al (21) demonstrated that the spontaneous parallel fluctuations in BP and PI were markedly reduced after surgery. Fazan et al (9) showed that sinoaortic deafferentation affected the spectral indexes of BRS, as well as the HR responses to changes in BP induced by phenylephrine and nitroprusside.…”
Section: Discussionmentioning
confidence: 97%
“…Intravenous administration of phenylephrine was chosen to elevate MABP because it does not have confounding effects on CBF (32) and is routinely used to study various pathologies due to hypertension (33,34). If CBF in vertically positioned mice increased as a result of increasing blood pressure, it would support a rightward shift in the CBF autoregulation curve, as illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Tethering catheters for artery and vein cannulation is a basic operation for BP recording and drug infusion in freely moving animals. Some published studies performed this work on mice using techniques modified from the rat [1,3,4], but there are still some limitations. With rats, catheters are usually tunneled subcutaneously, exteriorized between the scapulae, and fixed there by suturing to the nearby muscles and skin.…”
mentioning
confidence: 99%